Follow-up after curative treatment for colorectal cancer: longitudinal evaluation of patient initiated follow-up in the first 12 months - Batehup, Lynn; Porter, K.; Gage, H.; Williams, P.; Simmonds, P.; Lowson, E.; Dodson, L.; Davies, N.J.; Wagland, Richard; Winter, J.R.; Richardson, A.; Turner, A.; et al. (Springer, 2017)
Purpose: To compare patient-triggered follow-up (PTFU) for curatively treated colorectal cancer against traditional outpatient follow-up (OPFU). Methods: Questionnaires were mailed at four time points over one-year post-treatment to two prospectively-recruited cohorts: A, patients entering follow-up and receiving OPFU pre-implementation of PTFU; B, patients entering follow-up (FU) and receiving either OPFU (B1) or PTFU (B2) post-implementation of PTFU. Bi-variate tests were used to compare patient characteristics and outcomes eight months after entering follow-up (generic and cancer-specific quality of life (QoL), satisfaction). Regression analysis explored associations between follow-up model and outcomes. Resource implications and costs of models were compared. Results: Patients in Cohort B1 were significantly more likely to have received chemotherapy (p<0.001), radiotherapy (p<0.05), and reported poorer QoL (p=0.001). Having a longstanding co-morbid condition was the most important determinant of QoL (p<0.001); model of care was not significant. Patients were satisfied with their follow-up care regardless of model. Health service costs were higher in PTFU over the first year. Conclusions: PTFU is acceptable to patients with colorectal cancer and can be considered to be a realistic alternative to OPFU for clinically suitable patients. The initial costs are higher due to provision of a self-management (SM) programme and remote surveillance. Further research is needed to establish long-term outcomes and costs.